Analysis of the Quality of Early Childhood Education Services of the Bengkulu City Education and Culture Office in Managing and Developing Early Childhood Education Institutions (PAUD): Analisis Kualitas Pelayanan Bidang Pendidikan Anak Usia Dini Dinas Pendidikan Dan Kebudayaan Kota Bengkulu Dalam Mengelola, Membina, Lembaga Pendidikan Anak Usia Dini (PAUD) - Amina Amina; Heru Purnawan; Edi Darmawi (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to analyze the service quality of Early Childhood Education (PAUD) at the Bengkulu City Education and Culture Office in managing and fostering PAUD institutions. The research method used is qualitative with a descriptive approach. Data collection techniques were carried out through in-depth interviews, observation, and documentation. The research informants consisted of 12 people, including 1 informant from the Bengkulu City Education and Culture Office (Head of PAUD Division), 3 informants from the staff of the Bengkulu City Education and Culture Office, 2 informants from PAUD institution managers, and 6 informants from PAUD institution principals. The results showed that the service quality includes five dimensions: reliability, responsiveness, assurance, empathy, and tangible evidence. Supporting factors include the integrated Dapodik system, adequate staff competence, and support from local government policies. Inhibiting factors include limited human resources, lack of continuous training, and inadequate facilities and infrastructure. The conclusion is that the service quality still needs to be continuously improved, especially in the aspects of responsiveness and tangible evidence.